Controlled synthesis of aligned Bi2S3 nanowires, sharp apex nanowires and nanobelts with its morphology dependent field emission investigations - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Pandiraj, S.; Khare, Ruchita T.; More, Mahendra A. (Crystengcomm, 2013)
Well-aligned ultra-long Bi2S3 nanowire arrays with three kinds of apex morphology - abruptly sharpened apex, thin belt and flat - have been systematically fabricated on tungsten (W) foil by a facile hydrothermal method. The structural and morphological studies reveal formation of distinct tip morphologies, possessing high aspect ratio, single crystalline nature and growth along the orthorhombic [001] axis. A plausible growth mechanism has been proposed on the basis of observed experimental results. The field emission properties of Bi2S3 nanowires and sharp apex Bi2S3 nanowires are investigated. From the field emission studies, the values of the turn-on field, required to draw emission current density of similar to 0.1 mu A cm(-2), are observed to be similar to 2.01 and 1.21 V mu m(-1) for nanowires and sharp apex nanowires, respectively. Furthermore, ultra-long Bi2S3 nanowires are also grown on the W microtip (brush-like) from which very high emission current density similar to 11 mA cm(-2) has been drawn. These results are helpful for the design, fabrication and optimization of integrated field emitters using 1D nanostructures as cold cathode material.

CdS nanowires: ultra-long growth and enhanced field emission properties - Chavan, Padmakar G.; Kashid, Ranjit V.; Badhade, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Vaccum, 2014)
Here, we report the synthesis of ultra-long CdS nanowires with aspect ratio similar to 8 x 10(4) by simple route of thermal evaporation technique. A change in the vertical arrangement of quartz boats leads in to the synthesis of ultra-long CdS nanovvires via high degree of condensation. This technique is seen to be cost effective and easy. The growth of the nanowires is found to be increased very rapidly from few micrometers to few millimeters. The possible reason for the growth of the ultra-long CdS nanowires is discussed in detail. The turn-on field defined for the current density of similar to 0.1 mu A/cm(2) has been found to be similar to 1.4, 1.45, 1 and 0.17 V/mu m for specimen A, B, C and D (specimens A-D, synthesized by variation in synthesis parameters) respectively. The turn-on field of the specimen D (similar to 0.17 V/mu m) is found to be quite superior than the value reported for other CdS nanoforms which is very remarkable. Simple way of bulk fabrication leads to the low turn-on value which indicates a possible use of the present emitter in the micro/nanoelectronics devices. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Current stability; field emission; synthesis